Receiver angle diversity design for high-speed diffuse indoor wireless communications - Khoo, S; Zhang, W; Faulkner, G; O'Brien, D; Edwards, D (2001)
Diffuse wireless optical communications offer more robust optical links in terms of coverage and shadowing than line-of-sight links. However, they are more susceptible to multipath distortion, limiting high-speed performance. Angle diversity receivers can be used to combat the effects of multipath distortion albeit, at the cost of an increased path loss. The performance of an angle diversity receiver with 18-degree field-of-view receiver elements is reported. We have developed a channel simulation system capable of providing angularly resolved channel impulse response data. This is integrated with a receiver design model that allows path loss, dispersion and coverage to be calculated for various receiver topologies. The resulting bit error rate (BER) for different operating conditions are reported. Currently, we are developing a measurement system that will allow us to gather high-resolution angularly resolved channel data and this real data will then be integrated to the receiver design simulation system. In this paper we describe the use of simulated and measured channel data in designing angle diversity receiver structures.